Penerapan Konsep Arsitektur Perilaku Pasca Pandemi Pada Desain Pasar di Kabupaten Wajo - Mahusfah, Ilmanda Tegar; AS, Zulkarnain; Nursyam, Nursyam (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2024)
Abstrak_ The application of post-pandemic behavior architecture to traditional market buildings in Wajo Regency has become a forum for fulfilling trade sector activities that support programs to prevent the spread of viruses and healthy buildings. This research used descriptive method and literature study as a method for collecting data. The research object focuses on the application of post-pandemic behavior architectural designs to traditional market buildings in Wajo Regency. The design results obtained are traditional markets that are able to support buying and selling activities comfortably by fulfilling rules and the behavior of market users during the post-pandemic period. Keywords: Post Pandemic Architecture Concept, Market Design, designing concept.